Brominated flame retardants effect in MCF-7 cells: Impact on vitamin D pathway. Issue 219 (May 2022) - Sousa, Sara; Maia, Maria Luz; Pestana, Diogo; Teixeira, Diana; Ângelo-Dias, Miguel; Martins, Catarina; Borrego, Luís Miguel; Delerue-Matos, Cristina; Calhau, Conceição; Fernandes Domingues, Valentina; Faria, Ana
Graphical abstract: Highlights: HBB promotes MCF-7 cell proliferation, cell migration and hMMP-9 expression. BFRs affect expression of vitamin D pathway genes. PBT promotes cell cycle arrest in phase G2/M. HBCD, TBB and HBB alter breast cancer cell cycle in response to calcitriol. Abstract: Brominated flame retardants (BFRs) are persistent environmental pollutants, allowing a constant human exposure which carries several health risks, including the occurrence of breast cancer and vitamin D deficiency. Vitamin D inhibits cell growth and is negatively associated with breast cancer risk. The effect of BFRs in breast cancer and vitamin D pathway is still poorly understood. MCF-7 cells were treated with hexabromocyclododecane (HBCD), 2-ethylhexyl-2, 3, 4, 5-tetrabromobenzoate (TBB), hexabromobenzene (HBB) and pentabromotoluene (PBT) using short and long-term exposure protocols. Viability, proliferation, migration, cell cycle and gene expression were assessed. Gene expression of hVDBP and hCYP2R1 was also evaluated in hepatocytes. Long-term exposure of MCF-7 cells to HBB increased cell proliferation and migration, consequently increasing MMP-9 expression. The vitamin D pathway was also altered by BFRs: cells appeared less prepared to activate and transport vitamin D and the signaling, action and inactivation mechanisms were diminished in the presence of BFRs. Untreated MCF-7 cells showed cell cycle arrest in phase G0/G1 in the presence of activated vitamin D. However, when MCF-7 cells were exposed to BFRs, cell cycle was arrested in phase G2/M, possibly due to DNA damage. Nonetheless, calcitriol seems to be able to mitigate the effect of some BFRs exposure, e.g. PBT.